Konsep Etika Islam dalam Perspektif Pemikiran Nurcholish Madjid - Azmi, Muhyidin (JURNAL AL-AQIDAH, 2024)
This research is library research that makes books that discuss the themes studied as a source of data in research, as the object to be explored in this research is Nurcholish Madjid. Furthermore, the results of this study show that Nurcholish Madjid's thoughts on the concept of Islamic ethics are contained in his argument about the idea of discipline which in his view has a close relationship with the concept of obedience which has a very mature meaning in Islamic teachings. According to Nurcholish Madjid, discipline is not just a social attitude, but also a manifestation of an individual's belief and diversity towards God. In addition, the concept of Islamic ethics in Nurcholish Madjid's view is also contained in his interpretation of piety. Taqwa in Nurcholish Madjid's view is a religious attitude that will further guide a believer as an individual who has a noble character.